Site-specific performance of 68Ga-DOTATATE PET/CT in detecting tumors with ectopic adrenocorticotropic hormone secretion - Wang, Junhu; Luan, Zhonghua; Li, Ting; Guan, Xiaodong (Frontiers in Oncology, 2023)
Objective: The aim of this study was to assess the detection ability of 68Ga-DOTATATE in pulmonary versus extrapulmonary tumors with ectopic adrenocorticotropic hormone secretion (EAS). Methods: Images of 68Ga-DOTATATE PET/CT from 74 patients with suspected EAS were retrospectively reviewed. EAS tumors were confirmed in 39 patients through surgical resection or biopsy. Image findings were compared with the histopathological results. Results: EAS tumors were pathologically confirmed via surgery or biopsy in 39 patients. Among those 39 patients, 25 were with pulmonary neuroendocrine tumors (NETs), and the remaining 14 were with extrapulmonary NETs. 68Ga-DOTATATE PET/CT correctly identified the tumor in 26 patients, rendering an overall detection rate of 66.7%. On a site-based analysis, 68Ga-DOTATATE PET/CT correctly identified the EAS tumor in 13 of 25 patients with pulmonary NETs, yielding a detection rate of 52%; for the 14 patients with extrapulmonary NETs, 68Ga-DOTATATE PET/CT correctly identified the EAS tumor in 13, yielding a detection rate of 92.9%. The detection rate of 68Ga-DOTATATE was significantly higher in extrapulmonary NETs than in pulmonary NETs (92.9%% vs. 52%, P = 0.013). For the 13 patients with positive pulmonary NETs, the tumor SUVmax ranged from 1.1 to 7.4 with an average SUVmax of 3.1 ± 2.1. For the 13 patients with positive extrapulmonary NETs, the tumor SUVmax ranged from 2.7 to 21.8 with an average SUVmax of 9.9 ± 6.3. The tumor SUVmax was significantly higher in extrapulmonary tumors than pulmonary tumors (P = 0.015). The tumor size was smaller in pulmonary tumors than in extrapulmonary tumors, while the difference was not significant (P = 0.516). Conclusion: 68Ga-DOTATATE showed site-specific difference in detecting tumors with EAS secretion. Specifically, 68Ga-DOTATATE performed better in the extrapulmonary EAS tumors than in pulmonary ones with both higher detection rate and uptake. Combination of anatomic imaging techniques are necessary for the correct diagnosis of pulmonary EAS tumors.